Developing the Knowledge Workers Model for Core Competencies Management in Iraqi Higher Education Institutions - Mohammed, Khamees Naser; Alnoori, Abdulsalam Ali Hussein; Jasim, Ahmed Idan (Journal of Reviews on Global Economics, 2020)
This paper aims at developing the knowledge workers model for core competencies management via identifying the dimensions of the knowledge workers that are possibly related to the core competencies management. The primary motivations for the current research lies in those gaps represented of scientific and experimental studies in this scope, as well as for the purpose of increasing knowledge in this field. This theoretical research contributes to the development of the knowledge workers model based on its dimensions for core competencies management in Iraqi higher education Institutions. This research used quantitative approach by questionnaire was taken in collecting the data from the research community represented by some Iraqi higher education institutes samples that reached (256) questionnaires, which is about (80%), distributed to individually. The correlation coefficient (Spearman's) and Regression coefficient was relied on by using spss-ver.24. also the Knowledge-based Institutional theory was depended on explaining the results. The empirical analysis of the results was made using (Cronbach's alpha) to test the scales consistency of the validity of the consistency coefficient. The questionnaire was on a high consistency and validity. The results have largely supported the research model referring to the relationship of the knowledge workers have a good correlation and influence relationship in the core competencies management. Hence, this research could be of great use to the researchers, academics, professionals and policies makers.